Tackling and Handling Students’ Grammar Mastery on Passive Voices in A Higher Education: Quizizz Application Power - Dian Fadhilawati; Aslam Khan; Dwita Laksmita Rachmawati; Moh Mansur (Universitas Hamzanwadi, 2022)
This research aimed to boost the grammar mastery of 24 students, particularly Passive voices using the Quizizz application and to discover their reactions to the usage of that platform for learning and assessing Passive Voices at a Private University in Blitar. This research used a classroom action research design with the following procedures: planning, acting, observing and evaluating, and reflecting. The research results revealed that the usage of the Quizizz application increased the mastery of passive voices of 24 students from 54.75 in the Pre-action Test to 87.25 on the post-action test. Furthermore, the respondents responded positively toward the usage of the Quizizz platform to learn and assess Passive Voices. Referring to the findings, we can sum up that using the Quizizz Application in Passive Voice learning is extremely beneficial in improving the students' learning outcomes since the students can learn passive voice material such as they are playing games anywhere and anytime. Therefore, the researchers suggest that teachers or lecturers may apply this application to their classrooms to make fun and enjoyable learning for the students.